Transformasi sosial-ekonomi kelompok perempuan singkong: Studi kasus pemberdayaan komunitas dari pengasuh anak tkw menuju pengelolaan potensi lokal di desa sukowilangun, kecamatan kalipare, kabupaten malang - Mashanda, Vebya Yuwa Ayu; Afifah, Siti Noer; Maula, Syahda Anzila In’amil; Ma’rifah, Urfi Aisyatul (Maliki Interdisciplinary Journal, 2025)
This study discusses the transformation of socio-economic groups of women in Sukowilagun Village, Kalipare District, Malang Regency, who previously worked as caregivers for female migrant workers (TKW) towards economic empowerment based on local potential, especially in cassava management. This study aims to understand the process of community empowerment, supporting and inhibiting factors, and its impact on the welfare of the local community. This study discusses the socio-economic transformation of the women’s community in Sukowilagun Village, Kalipare District, Malang Regency, who initially acted as caregivers for female migrant workers (TKW) into a business group based on local potential, namely the cassava women’s community. This change was driven by the need for economic independence and optimization of natural resources available in the area. Through a community-based empowerment program, this group shifted from informal work as caregivers to Micro, Small, and Medium Enterprises (MSMEs) that process cassava, especially in the production of mokaf flour as an alternative to wheat flour. This study uses a qualitative approach with a case study method, involving observation, in-depth interviews to understand the dynamics of the changes that occur. The results of the study show that this transformation not only improves the economic welfare of local women, but also strengthens social solidarity and increases women’s role in village development. Key factors for the success of this change include government support, skills training, and wider market access. These findings confirm that community-based empowerment can be an effective strategy in improving women’s welfare and developing the local economy sustainably.